Pengaruh Edukasi Perawatan Luka Menggunakan Media Virtual Reality terhadap Pengetahuan Merawat Luka pada Keluarga Pasien di Ruang Sadewa 2 RSUP Surakarta - Lilis Nur Kusuma; Widiyono Widiyono; Etty Eriyanti (JOURNAL SAINS STUDENT RESEARCH, 2026)
Health education aims to improve patients' and families' understanding. The use of innovative media such as virtual reality is considered capable of providing a more interactive and immersive learning experience. The research aims to determine the effect of wound care education using virtual reality media on wound care knowledge among patients' families. This study used a pre-experimental design with a one-group pre-test-post- test. The sample was 32 respondents from families of patients with post-operative wounds. The sampling technique used purposive sampling. The research instrument used a wound care knowledge questionnaire developed from standard wound care operating procedures. The results were analyzed using the marginal homogeneity test. The level of knowledge before education was mostly inadequate for 20 respondents (62.5%), and after education, it increased to sufficient for 22 respondents (68.75%). The marginal homogeneity test yielded a p-value of 0.000, indicating an effect of wound care education using virtual reality on wound care knowledge among patients' families. Education using virtual reality effectively improved wound care knowledge among patients' families.